The Effect of Problem Solving and Problem Posing Models and Innate Ability to Students Achievement - Ratna Kartika Irawati (Jurnal Pendidikan Sains, 2014)
Pengaruh Model Problem Solving dan Problem Posing serta Kemampuan Awal terhadap Hasil Belajar Siswa Abstract: Chemistry concepts understanding features abstract quality and requires higher order thinking skills. Yet, the learning on chemistry has not boost the higher order thinking skills of the students. The use of the learning model of Problem Solving and Problem Posing in observing the innate ability of the student is expected to resolve the issue. This study aims to determine the learning model which is effective to improve the study of the student with different level of innate ability. This study used the quasi-experimental design. The research data used in this research is the quiz/test of the class which consist of 14 multiple choice questions and 5 essay questions. The data analysis used is ANOVA Two Ways. The results showed that Problem Posing is more effective to improve the student compared to Problem Solving, students with high level of innate ability have better outcomes in learning rather than the students with low level of innate ability after being applied with the Problem solving and Problem posing model, further, Problem Solving and Problem Posing is more suitable to be applied to the students with high level of innate ability.Key Words: problem solving, problem posing, higher order thinking skills, innate ability, learning outcomes Abstrak: Pemahaman konsep-konsep kimia yang bersifat abstrak membutuhkan keterampilan berpikir tingkat tinggi. Pembelajaran kimia belum mendorong siswa melakukan keterampilan berpikir tingkat tinggi. Penggunaan model pembelajaran Problem Solving dan Problem Posing dengan memperhatikan kemampuan awal siswa diduga dapat mengatasi masalah tersebut. Penelitian ini bertujuan untuk mengetahui model pembelajaran yang efektif dalam meningkatkan hasil belajar dengan kemampuan awal siswa yang berbeda. Penelitian ini menggunakan rancangan eksperimen semu. Data penelitian menggunakan tes hasil belajar yang terdiri atas 14 soal pilihan ganda dan 5 soal esai. Analisis data menggunakan uji ANOVA Two Ways. Hasil penelitian menunjukkan bahwa Problem Posing lebih efektif meningkatkan hasil belajar siswa dibandingkan Problem Solving, siswa berkemampuan awal tinggi memperoleh hasil belajar yang lebih baik dibandingkan dengan siswa yang berkemampuan awal rendah, serta Problem Solving dan Problem Posing lebih cocok diterapkan kepada siswa yang berkemampuan awal tinggi.Kata kunci: problem solving, problem posing, keterampilan berpikir tingkat tinggi, kemampuan awal, hasil belajar